Dedicated Verses and (Social) Interventions in the Poetry of John Pepper Clark - Afolayan, Kayode Niyi (SCHOLARS: Journal of Arts & Humanities, 2025)
Despite his transition in 2020, the ranking of contemporary poets in Nigeria today will reveal John Pepper Clark as the most prolific poet. This pedigree notwithstanding, his numerous compositions have received token attention compared to his contemporaries, such as Wole Soyinka, and other Nigerian poets of other generations. Among others, one critical reason that has been adduced for Clark’s less visibility is the eclectic nature of his poetry. This paper, in taking a closer look at some selected verses in the poetry volumes of Clark, navigates the social impulses in his poetry by isolating some of his “dedicated verses.” In validating the importance and centrality of “dedicated verses” to the poet, the paper delineated typologies and forms of his “dedicated verses” and outlined their relationship with the critical social issues in the postcolonial spaces he mirrored. The conclusion of the paper affirms the heterogonous credentials of Clark’s poetry, and argues that by paying attention to the “dedicated verses,” critics can have access, not only to the musings and inspirations which predicate his interventions on the conditions of dystopia but also get exposed to the poet’s commitment to the eradication of identified social ills and healing of those fractures that have ruptured his postcolonial space.